Exploring the Role of IT Usage in Enhancing Customer Satisfaction: A Literature Review on SMEs in the Creative Industries - Amar Ratnakar Naik; Ifta Firdausa Nuzula (The Indonesian Institute of Science and Technology Research, 2026)
Small and Medium-sized Enterprises (SMEs) in the creative industries play a critical role in driving innovation and economic growth. The adoption of Information Technology (IT) has become increasingly pivotal in enhancing their operational efficiency and customer engagement. This literature review explores the impact of IT usage on customer satisfaction within SMEs operating in the creative industries. It examines how IT tools, such as customer relationship management (CRM) systems, e-commerce platforms, and digital marketing, influence customer experiences and loyalty. Key findings indicate that effective IT adoption not only streamlines business processes but also fosters personalized interactions and improved service delivery, which are critical to customer satisfaction. Challenges such as limited resources, lack of technical expertise, and data security concerns are also discussed. The review concludes by highlighting the need for SMEs in the creative sector to leverage IT to remain competitive strategically and recommends areas for further research to optimize IT integration for enhanced customer satisfaction.